Overcapitalization and social norms of cooperation in a small-scale fishery - Schaap, Robbert; Richter, Andries (Ecological economics, 2019)
The increasing technological efficiency of harvesting equipment has been identified as one of the main causes of overcapacity and overexploitation of natural resources. In this paper, a formal model is developed which studies the effects of technological efficiency as an endogenous variable within a bioeconomic system. We model capital investments in a fishery, where investment decisions are made less frequently than the allocation of variable inputs. We study how the possibility to invest in capital affects open access dynamics, and also the evolution of cooperative harvesting norms. We find that the possibility to make large capital investments can destabilize cooperation, especially if enforcement capacity is low. Further, we find that communities can preserve cooperation by agreeing on a resource level that is lower than socially-optimal. This reduces the incentive to deviate from the cooperative strategy and invest in capital.